İNANÇ TURİZMİ BAĞLAMINDA SARATLI HALKININ HACI BEKTAŞ VELİ YILI FARKINDALIĞI - YAVUZ SELİM DENİZ; HAKKI ÇILGINOĞLU; MUHARREM AVCI (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2024)
Commemoration and Anniversaries Programs are one of the international programs organised by UNESCO. The aim of organising this program is to develop intercultural relations, introduce the people included in the program to the world. The respect of universe is one of the important criteria for the inclusion of Haji Bektash Veli in the UNESCO Programs. In this research, 30 people were interviewed using semi-structured interview techniques in the population of Saratlı Town of Aksaray province, data was interpreted by a descriptive analysis method. According to the purpose the research, the questions posed to the participants were collected under seperate headings, an attempt was made to determine their awareness of the 2021 Haji Bektash Veli Anniversary Year. The opinions of UNESCO on why 2021 was declared the Year of Haji Bektash Veli, the level and adequacy of the introduction of the Haji Bektash Veli Year were taken. According to the results of the research, while it was determined that their awareness of the UNESCO 2021 Haji Bektash Veli Year was high, it was revealed that the advertising activities for the Commemoration Year were insufficient.